THE LEVEL OF ACCOUNTING UNDERSTANDING OF MILLENIAL BUSINESSMAN IN EAST JAVA - Wenny Karuniawati; Husnunnida Maharani; Alfiana Fitri (Berkala Akuntansi dan Keuangan Indonesia, 2021)
The purpose of this study is to examine the effect of emotional intelligence which includes self-introduction, self-control, motivation, and empathy as well as learning behavior on the level of accounting understanding. The sample in this study used millennial businessmen in East Java. This research was conducted on 98 (ninety eight) millennial businessmen in 19 (nineteen) cities in East Java using purposive sampling technique. This study uses the statistical method of Partial Least Square (PLS). The results of this study indicate that self-control, empathy and learning behavior affect the level of accounting understanding. The implication of this research is that millennial businessmen should consider every impact of their actions, care for the surrounding environment, and read accounting material to increase knowledge related to accounting.